Takaful industry: a Malaysian experience / Nooraslinda Abdul Aris and Pm Dr Rohana Othman - Abdul Aris, Nooraslinda; Othman, Rohana (Research Management Institute (RMI), 2011)
Insurance has become a necessity for all individuals and businesses. Islam supports the concept of insurance, provided it does not contradict the tenets of Shari'ah. The Al-Qur'an has invoked Muslims to prepare for any misfortune. Islamic insurance or Takaful is based on mutual assistance, sharing of risk and cooperation among participants. This research focuses on Takaful operators in Malaysia, looking specifically at their business models and modus operandi. The research also looks into the Takaful operators' financial performance and growth over the last three years, i.e. from year 2007 to 2009. The findings of the study shows that the industry is still a green field or new growth area that requires widespread public awareness and education. The study also found regulations and standards in practice to ensure the growth of the Takaful industry are at par with world economics principles and perhaps can be built up as a mechanism to protect public interest and welfare in accordance to the Shari'ah.